Reprint of: The myth of conformity: Adolescents and abstention from unhealthy drinking behaviors. (January 2015) - Rees, Carter; Wallace, Danielle
Abstract: Adolescent peer groups with pro-drinking group norms are a well-established source of influence for alcohol initiation and use. However, classic experimental studies of social influence, namely 'minority influence', clearly indicate social situations in which an individual can resist conforming to the group norm. Using the National Longitudinal Study of Adolescent Health ("Add Health"), a nationally representative sample of adolescents, we find evidence that being a non-drinking adolescent does not unilaterally put youth at risk for drinking onset when faced with a friendship network where the majority of friends drink. Our results also show that a non-drinking adolescent with a majority of drinking friends is significantly less likely to initiate alcohol abuse if he or she has a minority of non-drinking friend(s). Furthermore, a drinking adolescent with a majority of friends who drink has a decreased probability of continuing to drink and has overall lower levels of consumption if he or she has a minority of friends who do not drink. Our findings recognize that adolescent in-group friendships are a mix of behavioral profiles and can perhaps help adolescents continue or begin to abstain alcohol use even when in a friendship group supportive of alcohol use. Highlights: Social influence during adolescence does not equate to conformity. Non-drinking adolescents can resist pro-drinking group norms. Drinking adolescents can also desist from drinking even when a majority of friends drink. In-group dissent can lead to healthy choices during adolescence.